The Portrayal of Gender in the ELT textbook issued by Non-Governmental Publisher in Indonesia - Hasanah, Uswatun; Ariyanto, Sugeng; Setyono, Budi (English Education Study Program, 2021)
The study was conducted to investigate the portrayal of gender in English Language Teaching (ELT) for senior high school in Indonesia. Critical Discourse Analysis (CDA) and Semiotic by Roland Barthes's (1977) framework was chosen as the tool to elaborate on how is gender represented through visual and textual material depicted. The finding reveal that the materials contain various gender issues such as stereotypes, imbalance, and inequality. However, several illustrations emerge from the positive image of a female. The textual study suggests that as English textbooks play an important role in transferring ideologies and values, therefore the textbook writer should pay more attention to the gender issues in the educational sector.